Pengaruh Pemanfaatan Aplikasi Canva sebagai Media Presentasi terhadap Hasil Belajar Siswa di SMK XYZ: Analisis Uji-T Berpasangan - Violeta Nirmala; Yuli Alam; Robi Krisna (MAMEN: Jurnal Manajemen, 2025)
A successful learning process requires adaptation to the diversity of students' characteristics, both in terms of learning styles and mastery of the material. The learning process in the use of digital media as learning materials is one relevant solution. Creative delivery of material can increase enthusiasm for learning. Canva is an easily accessible design platform that can be used to present learning materials in a visual and attractive way. This study was conducted to evaluate the extent to which the use of Canva as a presentation tool impacts learning outcomes at SMK XYZ. Learning outcomes were obtained from the same students who took pretest and posttest exams. The study used a quantitative approach, with a sample of 25 students who had undergone pretest and posttest treatments. Data were analyzed using a paired t-test via the SPSS application. The analysis results showed that the calculated t-value of -5.634 exceeded the critical t-value of 2.060 at a 5% significance level. These findings indicate a significant improvement in learning outcomes after the implementation of Canva in the learning process. In conclusion, the use of Canva not only enriches the visualization of materials but also encourages active student participation. Therefore, the implementation of creative digital media such as Canva is worth considering as a teaching strategy in vocational high school environments